2015
DOI: 10.1177/1479164114560910
|View full text |Cite
|
Sign up to set email alerts
|

The advanced glycation end product methylglyoxal-derived hydroimidazolone-1 and early signs of atherosclerosis in childhood diabetes

Abstract: Background: Advanced protein glycation is an important mechanism for the development of late diabetic complications including atherosclerosis. Methylglyoxal-derived hydroimidazolone-1 is the most abundant advanced glycation end product in human plasma. Aim: To investigate the relationship between methylglyoxal-derived hydroimidazolone-1 and early signs of atherosclerosis in children and adolescents with type 1 diabetes and healthy controls. Methods: A total of 314 diabetes patients aged 8-18 years were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…There is growing interest in detecting and quantifying individual AGE epitopes, as various AGEs may evoke different, even contradictory, responses in the body. 23 However, the available tools remain limited. Of these, immunoassays are likely to have a potential for a widespread application due to their relative simplicity and low cost, but the available ELISAs for AGEs are usually universal assays not dedicated to quantifying individual AGEs epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in detecting and quantifying individual AGE epitopes, as various AGEs may evoke different, even contradictory, responses in the body. 23 However, the available tools remain limited. Of these, immunoassays are likely to have a potential for a widespread application due to their relative simplicity and low cost, but the available ELISAs for AGEs are usually universal assays not dedicated to quantifying individual AGEs epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesise that AGE accumulation in IVDs is associated with IVD calcifications and that AGEs can directly induce hypertrophy and osteogenic differentiation of IVD cells. This hypothesis is based on the knowledge that AGE accumulation is associated with calcifications in vascular tissues (Hangai et al ., 2016; Heier et al ., 2015; Wang et al ., 2012) but has not been shown in the IVD or collagenous tissues. Our results indicated that the AGE MG-H1 was associated with ectopic calcifications in human IVDs from various degeneration stages and that MG-H1 was also associated with markers of endochondral ossification, hypertrophy and the involvement of RAGE.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed for Collagen 10 alpha-1 (COL10, concentration: 1:200; ab58632, abcam, Cambridge, MA, USA), a marker for hypertrophy, and osteopontin (OPN, concentration: 1:200; ab33046, abcam, Cambridge, MA, USA), a marker for osteogenic differentiation which is also expressed in atherosclerotic arteries and has been associated with vascular calcification in the IVD (Hristova et al ., 2011; Scatena et al ., 2007). AGEs were also assessed with immunostaining for methylglyoxal-hydroimidazolone (MG-H1, concentration: 1:250; STA-011, Cell Biolabs, San Diego, CA, USA), an AGE that is associated with atherosclerotic calcifications (Heier et al ., 2015) and the receptor for AGE (RAGE, concentration 1:200; ab37647, abcam, Cambridge, MA, USA), a trans-membrane receptor which has been associated with vascular calcification (Cecil et al ., 2011). De-plasticised sections were washed in distilled water, incubated for 5 min in Proteinase K (s3020, DAKO, Carpinteria, CA, USA), and followed by another wash. Non-specific binding was blocked with blocking solution (DAKO, Carpinteria, CA, USA) and incubated with the primary antibody for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In other studies, elevated levels of serum glycated albumin predicted major adverse cardio- and cerebral events in type 2 diabetic subjects [78], and in children with diabetes, elevated serum levels of methylglyoxal-derived hydroimidazolone were observed compared to age-matched control children, in parallel with increased C-reactive protein levels, suggestive of heightened inflammation [79]. …”
Section: Glycation and The Receptor Axis – Biomarkers For Diabetes Amentioning
confidence: 99%